The Perancangan Dashboard Berbasis Microsoft Excel Untuk Pengelolaan Keuangan (Studi Kasus : UMKM Mel Kitchen Malang) - Yosephina Dwita Ayuningtyas (Jurnal Satya Mandiri Manajemen dan Bisnis, 2025)
This research aimed to design a Microsoft Excel-based financial database and dashboard system tailored to the needs of MSME Mel Kitchen, a culinary business and the primary user of the system. The design focused on improving the efficiency and structure of its financial recording and management. The design focused on improving the efficiency and structure of its financial recording and management. Primary data were collected through interviews and observations to understand the user needs. The system was developed using the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). The results of the user needs analysis showed that the user needed a computerized financial data recording and visualization system to facilitate its financial management in a more structured and easy-to understand manner. Based on the analysis and development process, this research resulted in a Microsoft Excel-based financial database and dashboard system which consisted of several features such as sales input, expense tracking, cash flow monitoring, raw material inventory, outgoing stock management, and visual dashboards in the form of graphs and charts. Evaluation by both a technology expert and the end user confirmed that the system was feasible to use and effective for Mel Kitchen’s financial management needs.